Vergleich langfristiger Bevölkerungsvorausberechnungen für Deutschland - Hermann Buslei (Zentrum für Europäische Wirtschaftsforschung (ZEW); ZBW – Leibniz Information Centre for Economics, 1995)
In dieser Arbeit werden die Annahmen, deren Begründungen und die Ergebnisse von vier langfristigen Bevölkerungsvorausberechnungen für Deutschland (BIRG/FLÖTHMANN, BÖRSCH-SUPAN, Deutsches Institut für Wirtschaftsforschung, Statistisches Bundesamt) vergleichend gegenübergestellt. Der Vergleich der Ergebnisse beschränkt sich auf den Vergleich der vorausberechneten Gesamtbevölkerung und des Verhältnisses der über 60jährigen und älteren zu den 20- bis 59jährigen. – – This paper compares the assumptions, the projected total population and the population aged over 60 as percentage of population aged 20-59 of four selected longterm population forecasts for Germany. In all forecasts there were made plausible assumptions (at least plausible scenarios) about the factors determining future population: fertility, mortality and migration. The comparison shows the range of total population and old-age dependency expected by the authors and the sensitivity of the results by varying the assumptions in plausible ranges. As no assumption set was fully agreed to an alternative forecast was made. One variant of this forecast shows a higher old-age dependency than the other forecasts.
Keywords: 330